Epilepsy and Pregnancy: For healthy pregnancies and happy outcomes. Suggestions for service improvements from the Multispecialty UK Epilepsy Mortality Group. (August 2017) - Leach, J.P.; Smith, P.E.; Craig, J.; Bagary, M.; Cavanagh, D.; Duncan, S.; Kelso, A.R.C.; Marson, A.G.; McCorry, D.; Nashef, L.; Nelson-Piercy, C.; Northridge, R.; et al.
Abstract: Between 2009 and 2012 there were 26 epilepsy-related deaths in the UK of women who were pregnant or in the first post-partum year. The number of pregnancy-related deaths in women with epilepsy (WWE) has been increasing. Expert assessment suggests that most epilepsy-related deaths in pregnancy were preventable and attributable to poor seizure control. While prevention of seizures during pregnancy is important, a balance must be struck between seizure control and the teratogenic potential of antiepileptic drugs (AEDs). A range of professional guidance on the management of epilepsy in pregnancy has previously been issued, but little attention has been paid to how optimal care can be delivered to WWE by a range of healthcare professionals. We summarise the findings of a multidisciplinary meeting with representation from a wide group of professional bodies. This focussed on the implementation of optimal pregnancy epilepsy care aiming to reduce mortality of epilepsy in mothers and reduce morbidity in babies exposed to AEDs in utero . We identify in particular -What stage to intervene − Golden Moments of opportunities for improving outcomes -Which Key Groups have a role in making change -When − 2020 vision of what these improvements aim to achieve. -How to monitor the success in this field We believe that the service improvement ideas developed for the UK may provide a template for similar initiatives in other countries.